Ergonomic Analysis of Worker Postures in Waste Collection Job - Yussouff, A .A; Adedeji, K.A; Ismaila, S.O (International Journal of Management and Sustainability, 2017)
Most environments are characterized with the problem of waste disposal and management. The effect of waste collection method on the musculoskeletal disorders (MSDs) has been a challenge. Efforts had been intensified to reduce MSDs of workers through various ergonomic studies. The objective of this work is to undertake an ergonomic analysis of workers’ postures in waste collection job. Twenty five (15) employees of the parking and collection department of Lagos State Waste Management Authority (LAWMA) participated in the study. Their activities were video recorded while working and their postures was analyzed using Rapid Entire Body Assessment (REBA) sheet. Nordic questionnaire was also administered on the workers to obtain information on whether they experienced pain on any part of the body and the part of the body that the pain was experienced. The REBA action level classified postures into five levels as negligible risk, low risk, medium risk, high risk and very high risk of MSDs. Result showed that none of the workers were in the negligible risk, and low risk levels of MSDs. Further results showed that 6.66% were at medium risk; 26.7% were at high risk and 66.7% were at very high risk for the workers in the waste industry. The questionnaire revealed that 52% of the workers in both waste companies had pain in their neck and lower back during the last 12 months with the lower back being the most painful part in the body; 69.6% of them had wrist/hand pain; 65.2% had upper back pain which was the most painful part in the body during the last 7 days. It can be concluded that workers in waste collection job are subjected to MSDs as a result of the postures adopted while working.